IMMUNOGLOBULIN G4–RELATED OPHTHALMIC DISEASE MIMICKING INTRAOCULAR LYMPHOMA: A CASE REPORT. Issue Volume 16:Issues 1(2022) (January 2022) - Aragona, Emanuela; Miserocchi, Elisabetta; Arrigo, Alessandro; Marchese, Alessandro; Bordato, Alessandro; Bandello, Francesco; Modorati, Giulio
Abstract : Purpose: To describe a case of immunoglobulin G4–related choroiditis mimicking intraocular lymphoma. Methods: The patient underwent a complete ophthalmological evaluation including multimodal imaging, with structural optical coherence tomography, fluorescein angiography, indocyanine green angiography, ultra-widefield color, and autofluorescent fundus photographies to assess the ocular involvement. Results: Patient's best-corrected visual acuity was of 20/25 in the right eye and 20/20 in the left eye. Fundus appearance showed abnormal yellowish choroidal lesions and moderate vitritis in both eyes. Fluorescein angiography was within normal limits, whereas indocyanine green angiography showed areas of choroiditis in both eyes, and structural optical coherence tomography scans disclosed retinal small roundish lesions in the corresponding regions. Laboratory examinations and lymph node biopsy led to the final diagnosis of immunoglobulin G4–related disease. Conclusion: We describe a case of immunoglobulin G4–related choroiditis mimicking intraocular lymphoma. The proper use of multimodal imaging associated with laboratory investigations was helpful to reach the correct diagnosis. Abstract : This article describes choroidal localizations in immunoglobulin G4–related disease. Both systemic and fundus characteristics suggested the suspect of systemic and intraocular lymphoma. Multimodal imaging was an important tool to make the right diagnosis showing areas of bilateral choroiditis at indocyanine green angiography and roundish lesions at structural optical coherence tomography scans.